2022
DOI: 10.3991/ijim.v16i11.30103
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Time Diversity Gain – Comparison Between ITU-R P.618-13 Using a Concept of Rain Rate with Delay and Synthetic Storm Technique

Abstract: Future satellite companies will use higher Ka and V bands. Rain fade is the most important issue in establishing reliable communication between Earth and satellites outside the 10 GHz band. The problem is exacerbated in the tropics by significant rainfall throughout the year. One way to deal with rainfall attenuation is to use a time-diversity strategy. Real-time rainfall attenuation data is needed to analyze time variability. However, data from higher frequency bands such as Ka and V bands cannot be used. As … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…1 shows that calculated SST attenuation and rain rate time series have similar features. In earlier analysis, SST technique [28], [29] was implemented with different velocities from 1 to 20 m/s where it was found that the predicted rain attenuation characteristics match well with that of the measured rain rate at storm velocity of 11 m/s. The most important finding is that utilizing SST as a function of observed rainfall rate, attenuation rises quickly.…”
Section: A(x) = Kmentioning
confidence: 81%
See 2 more Smart Citations
“…1 shows that calculated SST attenuation and rain rate time series have similar features. In earlier analysis, SST technique [28], [29] was implemented with different velocities from 1 to 20 m/s where it was found that the predicted rain attenuation characteristics match well with that of the measured rain rate at storm velocity of 11 m/s. The most important finding is that utilizing SST as a function of observed rainfall rate, attenuation rises quickly.…”
Section: A(x) = Kmentioning
confidence: 81%
“…One minute integration time is needed to analyze data captured in 10 second integration time intervals. A conversion from mm/10 second to mm/hr is required [29]. As a result, the integration times were represented graphically using the…”
Section: Measurement and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation